THE COMPLEXITIES OF INTERPERSONAL CONFLICTS AS REFLECTED IN ERNEST HEMINGWAY’S THE KILLERS - -Putri Oktafiani, Adelia; -Nabilahtauzzahro Ibrahin, Laila; -Pujimahanani, Cahyaningsih; Utungga Pasopati, Rommel (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
The Killers is a short story written by Ernest Hemingway with Nick as the main character. The story centers on how fear is glorified through communications in this story. Nick, who is terrified of a word of death, tries to save Ole Anderson who is about to be killed. Nick tells the news to Ole, but he chooses to resign himself to his own death. Humans are filled with complex emotions and this short story indicates various matters of them in the response of death. This article would like to emphasize The Killers as direct reflection of complexities of interpersonal conflicts. By using qualitative methods, the analysis underlines complex ideas behind any communication. Language is not only related to communication, but also the intertwined meanings of known discourse. In conclusion, Hemingway’s short story involves various struggles of people who experience interpersonal conflicts around them.